Self-identity of Adolescents at the Lasiana Orphanage - Githy Dethan; Diana Aipipidely; Dian Lestari Anakaka (Journal of Health and Behavioral Science, 2021)
. In the process of forming self-identity, there are several factors that influence the process of forming self-identity, namely the influence of family on adolescent identity, the influence of cultural and ethnic identity and gender. The influence of family on the formation of adolescent self-identity is very important in the developmental period of adolescents who experience many changes in self-identity. This study aims to determine the effect of self-identity on adolescents at the Lasiana Orphanage, Kupang City in terms of gender. This type of research is a quantitative study. The sample size is 117 orphanage children who are willing to fill out the Coisoner scale. The type of research used is the comparative method, namely to determine the differences in identity among adolescents at the Lasiana Orphanage in terms of gender. The results of the Independent sample T-test stated that the self-identity of adolescents in the Lasiana orphanage in Kupang City, namely there was no significant difference. This is obtained from the sig (1-tailed) result of (0.086) (p> 0.05) so that H0 is rejected, meaning that there is no significant difference.